Elite mindset (a coaches` perspective on the tools athletes need to perform their best) - Wilkins, B. (Techniques Magazine, 2024)
Conversations around mental health have become more prevalent with each passing year. The stimas that once surrounded these topics are slowly fading as more individuals come forwards to share their stories. Many of these individuals are the athletes we watch compete each week. There individuals, whom we often place on a pedestal for their exceptional athletic abilites, face as many difficulties and struggles as anyone else. They hold themselves to such high standards that they relentrlessly pursure perfection, considering anything less than a personal best a failure. They grapple with the stress and anxiety of performing on the track and in the classroom, and some become so overwhelmed they fear performing at all. When we discuss talent, it´s evident that some athletes are naturally more gifted than others. As coaches, we don´t seek to provide them with additional talent; instead, we aim to nurture the talent they possess to help them reach their full potential. I believe the same approach should be applied when we consider "mental toughness." Some athletes are inherently more mentally resilient than others. Much like talent, they have what they have. However, what we can do is equip them with the mental tools they need to be ebtter prepared for any challenges they might face. "Mental toughness is built on doing the thing that is hard over and over again, especially when you don´t fell like it." (Afremow, 2013) By providing them with mental tools to add to their arsenal, we can ensure they are better prepared for whatever situations come their way. Each coach´s resources and circumstances differ. Some may have an entire staff of sports psychologists readily available to meet their athletes´ needs. Others might have just one on staff responsible for multiple athletes across numerous teams, and some coaches might be juggling so many roles that it besomes challenging to balance them all. Regardless of the circumstances, coaches spend the most time with their athletes daily. We should play an equally crucial role in their mental training as we do in their physical training. We are there with them in competition to congratulate them when things go well. And when they don´t, we need to be equipipped with the proper tools to help them navigate whatever situation they find themselves in.